Persaingan dalam Perbankan Syariah: Studi Perbandingan Kinerja Bank Syariah Swasta dan Pemerintah di Indonesia - Aisyah, Mitra Riani; Wahyudi Rusdi (Fakultas Ekonomi dan Bisnis Islam, 2024)
Comparing the financial performance between privately-owned Islamic banks and government-owned Islamic banks in Indonesia is the objective of this study. The analysis is conducted using key financial ratios such as Return on Assets (ROA), Operational Costs to Operational Income (BOPO), Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and Return on Equity (ROE). These ratios were selected because they provide a comprehensive overview of profitability, operational efficiency, capital adequacy, and the banks' ability to channel financing.The data analyzed were sourced from the annual financial reports of Islamic banks in Indonesia for a specific period. This study employs a quantitative approach using SPSS 25 software to process the secondary data. Based on the analysis conducted, the findings reveal that there are no significant differences between the financial performance of government-owned and privately-owned Islamic banks in terms of ROA, BOPO, FDR, and NPF. However, significant differences were found in the CAR and ROE ratios, indicating differences in capital management strategies and the ability to generate returns on equity.These differences are likely influenced by ownership structure and the management policies of each bank. This study provides valuable insights for stakeholders in understanding the dynamics of the financial performance of Islamic banks, both privately-owned and government-owned, which can be used as a basis for strategic decision-making by investors and regulators.